Fundamentals of equine podiatry: balanced trimming and physiological shoeing - Estrada, Manuel (2014)
The concepts of balanced trimming and physiological shoeing of the equine hoof as a way to prevent asymmetrical weight bearing and related orthopedic problems are discussed in this paper. Suggestions are given for the technical training of the personnel involved.  Considering the quantity and quality of the existing equine herd in Costa Rica, it is recommended to create a Farrier School as well as to coordinate the necessary efforts with other educational institutions related to the animal industry in order to bring the necessary knowledge to the groups involved in the care of the equine hoof.